Epidemiological profile of infertile couples in Western Iraq - Murshid, Rafal Mustafa; Al aany, Rehab; Ammar, Omar Farhan (Intelektual Pustaka Media Utama, 2024)
Infertility affecting approximately one in seven couples globally is a poorly documented issue in Iraq. This study examines the epidemiology of infertility among 82 Iraqi couples undergoing assisted conception at Al-Razzi Hospital in Ramadi. Retrospective analysis of medical records provided insights into sociodemographic profiles, infertility types (primary or secondary), and causes. The age range for males and females was 17-59 years, with means of 34.5 (±7.4) and 31.4 (±7.3) years, respectively. Infertility duration spanned a mean of 4.9 (±3.9) years. Primary infertility affected 74% of couples, while 25.6% experienced secondary infertility. Among the couples, the biochemical pregnancy rate was 45%, the clinical pregnancy rate was 38%, and the rate of live births was 24%. The average embryo transfer was 3.4, with a 21% miscarriage rate. This study emphasizes high rates of primary infertility dominated by female factors. Future research should consider larger population and detailed data on outcomes of in vitro fertilization (IVF) cycles to enhance understanding on the current (in)fertility status in Iraq.